Understanding Modern Nanotechnology: Insights into Its Evolution, Applications, and Global Impact - Laila, Umme; Akram, Muhammad; Khan, Fahad Said; Ozdemir, Fethi Ahmet; Umaru, Isaac John (Kwaghe International Journal of Sciences and Technology, 2025)
Nanoparticles, or ultrafine particles, are defined as particles with diameters ranging from 1 to 100 nanometers. As the core units of nanotechnology, these structures serve as the building blocks for integrating nanoscale materials into larger, functional systems. Over the past decade, nanotechnology has emerged as a transformative and interdisciplinary field, bridging advancements across a broad spectrum of domains, including medicine, materials science, energy, mechanics, plastics, optics, electronics, and aerospace. This paper provides an overview of the fundamental principles of nanotechnology, explores the unique properties of nanostructures, and highlights their current and potential applications across various scientific and industrial disciplines. By examining both foundational knowledge and emerging innovations, the study underscores nanotechnology’s expanding role in addressing complex challenges and shaping future technological development.